An urgent call for more ambitious ocean literacy strategies in marine protected areas: a collaboration project with small-scale fishers as a case study - Janire Salazar; Janire Salazar; Sílvia Gómez; Begoña Vendrell-Simón; Begoña Vendrell-Simón; Begoña Vendrell-Simón; Miroslav Pulgar; Núria Viladrich; Núria Viladrich; Núria Viladrich; Stefano Ambroso; Stefano Ambroso; et al. (Frontiers in Marine Science, 2024)
Cold-Water Corals play a paramount role in marine benthic ecosystems, increasing their complexity and providing spawning and nursery habitats to many species. However, due to their sessile lifestyle and ramified shape they are commonly entangled in nets and even by-caught during the practice of bottom-contact fishing, which includes impacts from both large-scale activities such as trawling and small-scale fishing (e.g., trammel nets or pots). In this context, passive and active restoration measures are crucial to avoid their damage and disappearance, which might cause the consequent loss of complexity and biodiversity of marine benthic communities. With the aim of modifying these fishing practices in the Marine Protected Area of Cap de Creus (North-Western Mediterranean), small-scale fishers and scientists (marine biologists) started a Participatory Process in which they agreed to develop a joint marine conservation program combining two distinct projects: a restoration project of the Cold-Water Corals incidentally captured on fishing nets for their subsequent reintroduction at sea (RESCAP project) and also a project on mitigation of fishing impacts on marine benthic communities (MITICAP project). Collaborative actions were carried out including interviews and exchanges of information with the purpose of collecting all the knowledge required for conducting the actions of the projects. This study shows the results of the assessment throughout five years (2017-2022) of cooperative work and highlights how crucial it is to develop long-term and revisable ocean literacy strategies for ensuring a sustainable ocean governance. An ocean literacy test evaluated the scientific knowledge of fishers at the end of the projects and revealed that despite all the efforts applied, still more work is needed, which reinforces the importance of improving the strategies of knowledge transfer for MPA management. Under the coordination of marine social anthropologists, a Cultural Consensus Analysis was conducted with the fishers. Results revealed a protoculture that should be characterized and considered when developing management strategies in the area. Additionally, the Personal Network Analysis showed that fishers have become agents of change and transmitted the learnings of the projects to their communities, fishers from nearby guilds, local educational centers and even the press. Furthermore, a list of recommendations is provided to optimize the multisector opportunities emerging from collaborative projects with marine scientists and fishers in MPAs.